Comparing the psychological well-being and job performance between male and female employees in Universiti Malaysia Sabah: covid-19 post pandemic study - Muhammad Ghazalie Mohamad Sabri; Razima Hanim Osman (Faculty of Psychology and Education, UMS, 2022)
The COVID-19 pandemic has a significant impact on individual’s psychological well-being and job performance. This study aimed to examine the relationship between psychological well-being and job performance among male and female employees at Universiti Malaysia Sabah (UMS) in the post-pandemic period. A total of 152 employees participated in an online survey that assessed psychological well-being (using Psychological Well-being Survey) and job performance (using the Individual Work Performance Questionnaire- IWPQ). Results of a t-test revealed that female employees had significantly higher levels of most psychological well-being dimensions (autonomy, environmental mastery, personal growth, relations with others and self-acceptance). However, no significant difference was found between male and female employees in term of purpose in life dimension in psychological well-being. Meanwhile findings showed that female employees had significantly higher levels of two dimensions in job performance (task performance and conceptual performance) but not significant in counterproductive work behavior dimension in job performance. These findings suggest that male and female employees do differ in psychological well-being and job performance in the post-pandemic period. To determine strategies for promoting the psychological well-being and job performance of all employees in the post-pandemic period, further research is required to investigate potential explanations for these findings.